Menorrhagia caused by severe hereditary factor VII deficiency - Aegerter, Ch.; Friess, D.; Alberio, L. (Hämostaseologie, 2003)
This report describes the clinical history and laboratory findings of three sisters with severe inherited factor VII deficiency. We present current knowledge about factor VII structure and function, and discuss clinical presentation as well as management options for patients affected by factor VII deficiency.
Keywords: Menorrhagia; FVII; FVII deficiency